(untitled) (Arquivos em Odontologia, 2024)
Aim: The aim of this study was to draw a stomatological profile of elderly patients treated at the Stomatology Service of a referral hospital in the city of Belo Horizonte, Minas Gerais – Brazil. Methods: Information was collected on the diagnostic hypotheses and definitive diagnoses of the elderly (aged 60 to 98 years) treated at the service, from September 2014 to December 2017. Results: Medical records of 1388 patients were evaluated, and 281 different diagnostic hypotheses were found. For males, there was a higher prevalence in both diagnostic and definitive diagnoses for benign and malignant epithelial neoplasms; In females, there was a higher prevalence, also in the hypotheses and diagnostic definitions, of inflammatory fibrous hyperplasia, related to the use of removable prostheses. Conclusion: Thus, this study evidenced the importance of knowledge about the main alterations that affect the oral cavity of elderly patients, which allows better attention to this population, besides being a pioneering stomatological study in hospital units.